Impacts of long-term service disruptions on passenger travel behaviour: A smart card analysis from the Greater Copenhagen area: Udvidet resumé - Eltved, Morten; Breyer, Nils; Ingvardson, Jesper Bláfoss; Nielsen, Otto Anker (Proceedings from the Annual Transport Conference at Aalborg University, 2021)
Disruptions in public transport are the major cause of passenger dissatisfaction (van Lierop et al., 2018) and they result in decreased public transport usage (Nazem et al., 2018). Much of the research on disruptions has focused on robustness of networks (Cats, 2016), network planning during disruptions (van der Hurk et al., 2016), and passenger information provision (Bruglieri et al., 2015). However, limited focus has been on understanding the changes to travel behaviour caused by planned long-term disruptions, such as closures due to construction work. Hence, this study analyses the effects of a long-term closure of an important suburban railway line in the Greater Copenhagen area (Denmark) on the travel behaviour of public transport passengers. Using a large-scale smart card dataset, the travel behaviour before and after the closure is compared and analysed across different groups of travellers focusing on changes to the travel patterns across groups.